Treatment of visceral hemorrhages with local vasoconstrictors - Martínez, Jorge; Sanguinetti, Julio; Carrera, Carlos; Ríos, Miguel; Arévalo, Ethel (Cirugía del Uruguay, 1977)
In the present work, the use of local vasconstrictors is tested, with a view to the primary treatment of severe low hematuria of bladder origin.